2008
DOI: 10.1007/s00464-008-9860-9
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life following vertical banded gastroplasty

Abstract: VBG not only leads to considerable weight loss, but also to significant improvements in HRQoL. However, some of the initially reported improvements lessened over time and not all patients appeared to profit in the same way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
2
6
0
2
Order By: Relevance
“…The baseline self-reported HRQOL was very poor and lower than the national norms in our series, as well in several other studies involving morbidly obese candidates for bariatric surgery [8,9,[12][13][14][15][16]. In the first year after surgery, we confirmed the highly significant rapid improvement in HRQOL observed in previous studies of LAGB [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The baseline self-reported HRQOL was very poor and lower than the national norms in our series, as well in several other studies involving morbidly obese candidates for bariatric surgery [8,9,[12][13][14][15][16]. In the first year after surgery, we confirmed the highly significant rapid improvement in HRQOL observed in previous studies of LAGB [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies investigating HRQOL in morbid obese candidates for bariatric surgery uniformly confirmed that these patients have HRQOL levels significantly lower than the corresponding national norms [8,9,[12][13][14][15][16]. HRQOL is a complex item and refers to the overall effects of medical conditions on physical, mental, and social functioning and well-being, as subjectively evaluated and reported by the patient [17].…”
mentioning
confidence: 99%
“…This phenomenon has been shown in previous studies [6, 9, 26, 29, 32, 33]. The present study shows the same trend; 1 year after surgery, practically all values in the HRQoL analysis were significantly improved while after 7 years this was reduced to about half of the values.…”
Section: Discussionsupporting
confidence: 91%
“…After long-term follow-up HRQoL decreases but remains significantly better compared to preoperative values [810, 1820, 2327]. Although some studies report that variables like gender, marital status, and sport activities are significant factors in HRQoL results [28, 29] most studies agree that improvement and deterioration of HRQoL are mainly associated with the magnitude of weight loss and weight regain, respectively [8, 9, 1820, 23, 24, 26, 27, 30, 31]. This is confirmed in the present study; significant correlations between weight loss and improvement of eight of the 13 HRQoL domains were found.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery requires lifelong compliance with behavior changes by the patient to maintain the weight loss [40]. Following bariatric surgery, improvements are found in personality features, psychopathology, depressive symptoms, body image, eating behavior, social functioning, and HRQoL; most improvements are seen in the first one or two years after surgery [41]. However, studies show great variation in outcome, and, unfortunately, bariatric surgery does not lead to identical results in every patient.…”
Section: Bariatric Surgerymentioning
confidence: 99%